Dynamic Incentives and the Optimal Delegation of Political Power - Le Borgne, Eric (IMF Working Papers; Working Paper ;, 2007)
This paper proposes a theory to explain why a politician delegates policy tasks to a technocrat in an independent institution. It formalizes the rationales for delegation highlighted by Hamilton (1788) and by Blinder (1998). Delegation trades-off the cost of having a possibly incompetent technocrat with a long-term job contract against the benefit of having a technocrat who (i) invests more effort into the specialized policy task and (ii) is better insulated from the whims of public opinion. One natural application of the theory is in the field of monetary policy where the model provides a new theory of central bank independence.